Population-level shape variation and otolith asymmetry in Diplodus annularis - Spani Federica; Kroha Silvio; Scacco Umberto; Di Giulio Andrea; Scalici Massimiliano (Scientific Reports)
Abstract Sound detection in fishes relies on the inner ear and peripheral structures, such as calcareous otoliths, which play a crucial role in perceiving movement, orientation, and balance. Otoliths, in particular, respond to various environmental factors including temperature, salinity, and food availability, making them valuable indicators of ecological conditions. This study applies geometric morphometrics (GMM) to analyze the otolith shape of Diplodus annularis (Linnaeus, 1758) from two distinct populations located in the Gulf of Asinara (Porto Torres, Sardinia) and the northern Adriatic Sea (Le Tegnue). By using GMM techniques, precise and quantifiable differences in otolith morphology were revealed between the two populations, demonstrating significant shape variation. In addition, fluctuating asymmetry (FA), which serves as a marker for developmental stability and environmental stress, was assessed. The results show marked disparities in FA between the populations: samples from Porto Torres exhibited posterior asymmetry, while samples from Le Tegnue showed asymmetry in the anterior region of the otoliths. These findings underscore the sensitivity of GMM in detecting even subtle morphological differences, making it a powerful tool for studying environmental and genetic influences on marine species.